Determinant Minat Mahasiswa Akuntansi Dalam Memilih Karir Menjadi Akuntan (Studi Kasus Mahasiswa Ekonomi Akuntansi Universitas Jambi) - Hurriyah Hurriyah; Mukhzarudfa Mukhzarudfa; Gandy Wahyu Maulana Zulmas (Trending: Jurnal Manajemen dan Ekonomi, 2023)
This study aims to identify and analyze labor market considerations, gender, work environment, personality and financial reward considerations for accounting student interest in choosing a career as a tan and analyze. The research hypothesis was tested using a multiple regression analysis model. Based on the results of the research described in the previous discussion, several conclusions can be drawn, namely Based on the regression results that considerations of the labor market, gender, work environment, personality and considerations of financial appreciation simultaneously have a significant effect on the interest of accounting students in choosing a career as an accountant, labor market considerations have an effect significant effect on the interest of accounting students in choosing a career as an accountant, gender has no significant effect on the interest of accounting students in choosing a career as an accountant, family environment has no significant effect on the interest of accounting students in choosing a career as an accountant, personality has a significant effect on the interest of accounting students in choosing a career as an accountant and financial rewards have no significant effect on the interest of accounting students in choosing a career as an accountant.